The Influence Of Trust, Security, Risk Perception And Information Quality On Customer Loyalty On The Bukalapak E-Commerce Site With Customer Satisfaction As Moderation Variable - Mujiyana Mujiyana; Sahni Damerianta; Putri Perdana Nurzikriah (International Humanities and Applied Science Journal, 2022)
The development of information technology is very rapid and provides many impacts on people's lives, including business on the internet, that is online commerce (e-commerce) is a way of selling or buying goods or services online. One of them is Bukalapak, the leading online shopping place in Indonesia that sells goods and services. The purpose of this study was to determine the effect of trust, security, risk perception and information quality on loyalty with satisfaction as a moderating variable on the Bukalapak e-commerce site. The type of data used in this study is primary data with 150 respondents. Testing is done with SPSS 21. At the analysis stage through validity, reliability, normality, multicollinearity, heteroxedasticity, regression tests with Modereted Regression Analysis (MRA) , test the coefficient of determination and t test. The results showed that the variables of trust and risk perception did not affect customer loyalty on the Bukalapak site while the security and quality of information affected customer loyalty. Customer satisfaction acts as a moderating trust, security, risk perception and quality of information on customer loyalty